(untitled) (Health Renaissance, 2017)
Background: Intestinal anastomosis is essential to maintain the continuity after resection. There has been constant controversy due to various repair options. Adequate apposition can be achieved by either single- or double-layer anastomosis which may affect the post-operative outcome. Objective: To compare the outcome of single-layer versus double-layer anastomosis of small and large intestine. Method: This prospective comparative study was conducted over a period of 16 months, and included 78 patients who underwent intestinal anastomosis (without diverting stoma) after fulfilling inclusion and exclusion criteria. They were randomized into double-layer and single-layer intestinal anastomosis groups by a computer generated series. Double layer anastomosis was constructed using inner continuous Polyglactin 3-0 and outer interrupted Silk 3-0, while single layer anastomosis was done with interrupted PDS 2-0. Result: The mean age was 39.79±17.78 years. A total of 59% were operated in emergency room while 41% in elective setting. Overall mean time for anastomosis was 31.81±6.03 (21-50) minutes. In double- and single-layer intestinal anastomosis mean time was 34.35±5.80 (26-50) and 29.13±5.08 (21-45) minutes respectively, which was statistically significant (p value < 0.05). Single-layer was completed 5 minutes earlier than double layer anastomosis in average. Clinical anastomotic leak was seen in six (7.7%) patients, three in each group. Eight (10.3%) patients had surgical site infection: 3 in double-layer and 5 in single-layer groups. One (1.3%) mortality was seen, from single-layer anastomosis group. Conclusion: Single-layer anastomosis can be constructed in significantly shorter time with similar complication rate when compared to doublelayer anastomosis. Health Renaissance 2015;13(2): 134-143